2017
DOI: 10.3390/su9111952
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability in Chinese Higher Educational Institutions’ Social Science Research: A Performance Interface toward Efficiency

Abstract: Sustainability issues in higher educational institutions' (HEIs) research, especially in the social science field, have attracted increasing levels of attention in higher education administration in recent decades as HEIs are confronted with a growing pressure worldwide to increase the efficiency of their research activities under a limited volume and relatively equitable division of public funding resources. This paper introduces a theoretical analysis framework based on a data envelopment analysis, separatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The preceding is a sample of how educational institutions make their decisions by building an action model that allows them to focus on counteracting the effects of the environment (Baum & Dahlin, 2007). Finally, for scholars like Wang and Hu (2017), universities' learning processes are part of the analysis they can conduct at the regional level. This process marks the path to follow to achieve better levels of reputation.…”
Section: Learning Process From Environment Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The preceding is a sample of how educational institutions make their decisions by building an action model that allows them to focus on counteracting the effects of the environment (Baum & Dahlin, 2007). Finally, for scholars like Wang and Hu (2017), universities' learning processes are part of the analysis they can conduct at the regional level. This process marks the path to follow to achieve better levels of reputation.…”
Section: Learning Process From Environment Dynamicsmentioning
confidence: 99%
“…It has been found that regardless of the nature of the institution, be it public or private, the quality of teaching and the level of production in research papers remains sustained due to the constant financing of public and private entities (Lee, 2011). Other research has shown substantial differences at the regional and country levels; even the dynamics will depend on the field of knowledge being analyzed (Wang & Hu, 2017). Thus, the literature has shown that universities with a broader knowledge structure will perform better than those that specialist universities characterize.…”
Section: Learning Process From Environment Dynamicsmentioning
confidence: 99%
“…Wals (2014) mentions that some universities find sustainability as an additional way of profiling and organizing themselves. However, the sustainability of universities can be promoted by skilled persons such as researchers, students, and academics, who have been viewed as the key component of sustainable development strategies by institutions and nations (Wang & Hu, 2017;Hodges et al, 2020). ESD is an approach that promotes interdisciplinary learning, problem-solving, critical thinking, and active learning to address sustainability challenges at various levels (UNESCO, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Innovative research achievements, such as new knowledge, theory, and patents are the strong foundation for the sustainable development of higher education. In this sense, the sustainability of universities can be promoted by means of research [2]. Skilled persons such as researchers, students, and academics have been viewed as the key component of sustainable development strategies by institutions and nations [3].…”
Section: Introduction 1research and Higher Education Sustainabilitymentioning
confidence: 99%
“…To be specific, this mixed-method study is intended to answer two questions: (1) what are the factors influencing Chinese RECAs' research performance? and (2) what is the prevalence of each factor? The RECAs in this research refers to the Chinese academics who are within six years (by 2019) of having obtained PhD degrees from universities not located in mainland China and having been appointed to academic positions in Chinese universities.…”
Section: Introduction 1research and Higher Education Sustainabilitymentioning
confidence: 99%